Professionalism and Entrepreneurial Action Housekeeper Hotel - Sulaiman, Debbi; B.Limbing, Lexi Pranata (Jurnal Entrepreneur dan Entrepreneurship, 2019)
The purpose of this study is to determine the performance of hotel housekeeper professionalism and entrepreneurial action. The research method used a qualitative approach. Data were collected using interviews and observations. For data analysis, the present study used the technique of Miles and Huberman (1994). This study found that entrepreneurial action from hotel housekeepers was identified by a number of attributes such as passion, open mindedness to change, teamoriented attitude, competence and ability towards housekeeping, interpersonal skills, ability to control personal emotions, professional ethics, leadership spirit and perfectionist.